Modele relacji między państwem a Kościołem Rzymskokatolickim w świetle przesłania Konstytucji duszpasterskiej o Kościele w świecie współczesnym Gaudium et spes - Machalski, Paweł (Fides, Ratio et Patria. Studia Toruńskie, 2016)
The article contains an extensive analysis of the message of the Pastoral Constitution on the Church in the Modern World – Gaudium et Spes – one of the key documents of the Second Vatican Council. Research problems boil down to the following questions: Which model of state-Church relations is preferred by the Holy See? To what extent the recommendations of the Council Fathers were recognized by the Civil Authorities of countries whose citizens are mostly Catholics? To what extent these opinions were incorporated into the regulations of their domestic law, including confessional rules of constitutions?The paper consists of three parts. The first of these includes analysis of the origin, meaning and structure of Gaudium et Spes, as well as outline historical models of Church-State relations before the Second Vatican Council. The second part relates to the doctrine – the interpretation of three principles, which define the optimal relations of both orders – sacrum and profanum – according to the Council Fathers. Finally, the third part contains an analysis of the practical manifestation of State-Church relations, giving the example of Poland, Germany and Italy – countries which incorporate in their legal system, mentioned before, the principles of friendly separation (coordinated separation) – recommended by the Second Vatican Council.